Characterization of persistent concussive syndrome using injury reconstruction and finite element modelling. (January 2015) - Post, Andrew; Kendall, Marshall; Koncan, David; Cournoyer, Janie; Blaine Hoshizaki, T.; Gilchrist, Michael D.; Brien, Susan; Cusimano, Michael D.; Marshall, Shawn
Abstract: Concussions occur 1.7 million times a year in North America, and account for approximately 75% of all traumatic brain injuries (TBI). Concussions usually cause transient symptoms but 10 to 20% of patients can have symptoms that persist longer than a month. The purpose of this research was to use reconstructions and finite element modeling to determine the brain tissue stresses and strains that occur in impacts that led to persistent post concussive symptoms (PCS) in hospitalized patients. A total of 21 PCS patients had their head impacts reconstructed using computational, physical and finite element methods. The dependent variables measured were maximum principal strain, von Mises stress (VMS), strain rate, and product of strain and strain rate. For maximum principal strain alone there were large regions of brain tissue incurring 30 to 40% strain. This large field of strain was also evident when using strain rate, product of strain and strain rate. In addition, VMS also showed large magnitudes of stress throughout the cerebrum tissues. The distribution of strains throughout the brain tissues indicated peak responses were always present in the grey matter (0.481), with the white matter showing significantly lower strains (0.380) ( p <0.05). The impact conditions of the PCS cases were severe in nature, with impacts against non-compliant surfaces (concrete, steel, ice) resulting in higher brain deformation. PCS biomechanical parameters were shown to fit between those that have been shown to cause transient post concussive symptoms and those that lead to actual pathologic damage like contusion, however, values of all metrics were characterized by large variance and high average responses. This data supports the theory that there exists a progressive continuum of impacts that lead to a progressive continuum of related severity of injury from transient symptoms to pathological damage.